Sleep Quality Is Related to Health and Skills - Wahid, Wahyana Mujari (Jurnal Pendidikan Jasmani (JPJ), 2023)
The formulation of the problem in this research is to find out how physical fitness correlates with health and skills with sleep quality. The aim of this research is to find out whether there is a relationship between fitness and health and skills with sleep quality. The type of research used in this research is quantitative descriptive research with a correlational research plan and design. In this research design, the research sample was selected by purposive sampling based on certain characteristics to become one overall sample. One of the aims was that in this research the research sample was homogeneous. The total sample in this study was 18 samples who were Hippocrates FK Unhas futsal athletes aged 16-20 years. Based on the results of data analysis of the relationship between physical fitness in relation to health and skills and sleep quality, the results of the correlation test were obtained, namely that there was a relationship between physical fitness in relation to health and sleep quality with the Pearson correlation coefficient between variables, namely (r) = 0.203 with a significance level of 0.007 ( p<0.05) and the results of the correlation test were obtained, namely that there was a relationship between physical fitness in relation to fitness and sleep quality with the Pearson correlation coefficient between variables, namely (r) = 0.821 with a significance level of 0.006 (p<0.05). So, it can be concluded that there is a significant relationship between physical fitness, both related to health and skills, with sleep quality.